The effect of pH on chronic aquatic nickel toxicity is dependent on the pH itself: Extending the chronic nickel bioavailability models. (25th February 2016) - Nys, Charlotte; Janssen, Colin R.; Van Sprang, Patrick; De Schamphelaere, Karel A.C.
Abstract: The environmental quality standard for Ni in the European Commission's Water Framework Directive is bioavailability based. Although some of the available chronic Ni bioavailability models are validated only for pH ≤ 8.2, a considerable fraction of European surface waters has a pH > 8.2. Therefore, the authors investigated the effect of a change in pH from 8.2 to 8.7 on chronic Ni toxicity in 3 invertebrate ( Daphnia magna, Lymnaea stagnalis, and Brachionus calyciflorus ) and 2 plant species ( Pseudokirchneriella subcapitata and Lemna minor ). Nickel toxicity was almost always significantly higher at pH 8.7 than at pH 8.2. To test whether the existing chronic Ni bioavailability models developed for pH ≤ 8.2 can be used at higher pH levels, Ni toxicity at pH 8.7 was predicted based on Ni toxicity observed at pH 8.2. This resulted in a consistent underestimation of toxicity. The results suggest that the effect of pH on Ni 2+ toxicity is dependent on the pH itself: the slope of the pH effect is steeper above than below pH 8.2 for species for which a species‐specific bioavailability model exists. Therefore, the existing chronic Ni bioavailability models were modified to allow predictions of chronic Ni toxicity to invertebrates and plants in the pH range of 8.2 to 8.7 by applying a pH slope (SpH ) dependent on the pH of the target water. These modified Ni bioavailability models resulted in more accurate predictions of Ni toxicity to all 5 species (within 2‐fold error), without the bias observed using the bioavailability models developed for pH ≤ 8.2. The results of the present study can decrease the uncertainty in implementing the bioavailability‐based environmental quality standard under the Water Framework Directive for high‐pH regions in Europe. Environ Toxicol Chem 2016;35:1097–1106. © 2015 SETAC